The Role of Anti-Racist Community-Partnered Praxis in Implementing Restorative Circles Within Marginalized Communities in Southern California During the COVID-19 Pandemic. Issue 2 (March 2023) - Adkins-Jackson, Paris B.; Vázquez, Evelyn; Henry-Ala, Frank K.; Ison, Juliana M.; Cheney, Ann; Akingbulu, Josephine; Starks, Christian; Slay, Lindsay; Dorsey, Alexander; Marmolejo, Connie; Stafford, Alvin; Wen, James; et al.
The COVID-19 pandemic has exacerbated the adverse influence of structural racism and discrimination experienced by historically marginalized communities (e.g., Black, Latino/a/x, Indigenous, and transgender people). Structural racism contributes to trauma-induced health behaviors, increasing exposure to COVID-19 and restricting access to testing and vaccination. This intersection of multiple disadvantages has a negative impact on the mental health of these communities, and interventions addressing collective healing are needed in general and in the context of the COVID-19 pandemic. TheS hare, T rust, O rganize, andP artner COVID-19 California Alliance (STOP COVID-19 CA), a statewide collaborative of 11 universities and 75 community partners, includes several workgroups to address gaps in COVID-19 information, vaccine trial participation, and access. One of these workgroups, the Vaccine Hesitancy Workgroup, adopted an anti-racist community-partnered praxis to implement restorative circles in historically marginalized communities to facilitate collective healing due to structural racism and the COVID-19 pandemic. The project resulted in the development of a multilevel pre-intervention restorative process to build or strengthen community–institutional partnerships when procurement of funds has been sought prior to community partnership. This article discusses this workgroup's role in advancing health justice by providing a community-based mental health intervention to marginalized communities in Southern California while using an antiracist praxis tool to develop a successful community–institutional partnership and to live up to the vision of community-based participatory research.